ANALISIS SAMPUL BUKU TEMA “ UDARA BERSIH BAGI KESEHTAN”: ANALISIS SAMPUL BUKU TEMA “ UDARA BERSIH BAGI KESEHTAN” - NurAyu Winingsih; Moh. Kadhapy (LPPM UNiversitas Bina Mandiri Gorontalo, 2022)
Textbooks are textbooks or commonly referred to as teaching guides that are used as books in certain fields of study, and for instructional purposes and purposes, equipped with teaching tools that are compatible and easily understood by the users. The function of textbooks is as reference material for teachers and students and can make it easier for teachers to convey material. Textbooks aim to help communication between teachers and students. Textbooks are known by various names, such as textbooks, material books, and textbooks. In this study, researchers used a method, namely a qualitative approach method in presenting descriptive data. This method is carried out through analyzing and interpreting in depth the design principles contained in the integrated thematic book of the 2013 curriculum for class V entitled CLEAN AIR FOR HEALTH from the aspects of shape, color, and illustration composition layout. On the cover of the book, it is equipped with illustrations in the form of pictures, where these pictures can provide an overview of the contents of the book. From the statement on the analysis of the thematic textbook covers above, it can be concluded that the thematic textbook entitled (Clean Air for Health) is about research from the concept of the book, the color of the book, and the cover design of this book illustration meet the criteria for proper use. Starting from the form of book writing that is easy for students to understand and illustrative pictures that are suitable for use for fifth grade elementary school children.